Relevance of TP53 for CLL diagnostics. Issue 5 (2nd February 2019) - Catherwood, Mark A; Gonzalez, David; Donaldson, David; Clifford, Ruth; Mills, Ken; Thornton, Patrick
Abstract : TP53 disruption in chronic lymphocytic leukaemia (CLL) is a well-established prognostic marker and informs on the appropriate course of treatment for patients. TP53 status is commonly assessed by fluorescence in situ hybridisation for del(17 p) and Sanger sequencing for TP53 mutations. At present, current screening methods for TP53 mutations fail to detect diagnostically relevant mutations potentially leading to inappropriate treatment decisions. In addition, low levels of mutations that are proving to be clinically relevant may not be discovered with current less sensitive techniques. This review describes the structure, function and regulation of the TP53 protein, the mutations found in cancer and CLL, the relevance of TP53 disruption in CLL and the current screening methods for TP53 mutations including next-generation sequencing.